Intraspecific genetic variation in the common midwife toad (Alytes obstetricans): subspecies assignment using mitochondrial and microsatellite markers. (12th November 2013) - Maia‐Carvalho, Bruno; Gonçalves, Helena; Martínez‐Solano, Iñigo; Gutiérrez‐Rodríguez, Jorge; Lopes, Susana; Ferrand, Nuno; Sequeira, Fernando
Abstract The common midwife toad (Alytes obstetricans), widely distributed in the northern half of the Iberian Peninsula and part of Western Europe, is currently subdivided into four subspecies: A. o. obstetricans, A. o. boscai, A. o. pertinax and A. o. almogavarii. However, the delimitation of these subspecies and their ranges are still under discussion because strong discordances have been found between morphological and molecular data, and especially among different genetic markers. Here, we screen a set of novel microsatellite loci and mtDNA sequences of A. obstetricans populations representative of all currently recognized subspecies to investigate the correspondence between genetic groupings inferred from clustering analysis of microsatellite genotypes and the described subspecies and test whether patterns of mtDNA variation are concordant with those genetic clusters. Our results confirm previous expectations of extremely high intraspecific diversity in A. obstetricans in Iberia. Analyses of microsatellite and mtDNA data were concordant in recovering five well‐defined groups, of which three correspond to previously defined subspecies, while the two additional clusters correspond to populations of subspecies A. o. boscai separated by the Douro River. Our results suggest the occurrence of two distinct genetic units within A. o. boscai that likely result from a long independent evolutionary history, thus deserving special attention from a conservation point of view.